MANAJEMEN SARANA PRASARANA PENDIDIKAN DALAM MENINGKATKAN PROSES PEMBELAJARAN DI TK KEMALA BHAYANGKARI 82 KOTA MAGELANG - syari ati masyithoh (Jurnal CARE (Children Advisory Research and Education), 2020)
Facilities Education infrastructure that is well managed and adequate will affect the learning process in an educational institution. The method used in this research is descriptive with a qualitative approach. This study aims to describe the management of educational facilities and infrastructure in improving the quality of learning at TK Kemala Bhayangkari 82 Magelang City. Data collection techniques include: observation, interview, and study documentation. The subjects of the research are the principal, teachers and school operators. The results of this study indicate that there are five processes in the management of infrastructure at the Kemala Bhayangkari 82 Kindergarten in Magelang City. The process includes: 1) Planning, namely the activity of analyzing all educational facilities and infrastructure needed. 2) Procurement of Sarpras sourced from reparations, government funds, student guardians, and foundations. 3) Inventory of Sarpras is the recording of the code, quantity, price of goods and others aimed at controlling school facilities and infrastructure. 4) Maintenance of sarpras through daily maintenance by involving students and teachers whose targets are story books, classrooms, educational play equipment. The periodic maintenance includes maintaining the school building and outdoor educational play equipment. 5) Elimination of infrastructure as the last stage, which is carried out on facilities and infrastructure that have been damaged or lost.